Evaluation of a hepatitis B vaccination program in Taiwan: impact on hepatocellular carcinoma development. (January 2010) - Chemin, Isabelle
Evaluation of: Chang MH, You SL, Chen CJ et al. ; Taiwan study group: Decreasedincidence of hepatocellular carcinoma in hepatitis B vaccinees: a 20 years followupstudy. J. Natl Cancer Inst. 101, 1348––1355 (2009). This population-based studyaimed to investigate whether a universal Taiwanese program, launched in 1984, has been able to prevent hepatocellular carcinoma (HCC) beyond childhood.The Incidence of HCC in Taiwan from 1983 to 2004 was assessed through twonational cancer registries where age and sex-specific incidence were comparedamong a vaccinated and unvaccinated birth cohort with regression models. Thisstudy further characterized the 64 vaccinated cases that developed HCC inorder to discriminate specific risk factors.